Orthorhombic polymorph of 1,2-bis(2-aminophenoxy)ethane - Heinemann, Frank Wilhelm; et al. (Acta Crystallographica Section E: Structure Reports Online, 2007)
The orthorhombic polymorph of the title compound, C14H16N2O2, is devoid of crystallographically imposed molecular symmetry. The crystal structure is stabilized by N - (HO)-O-... hydrogen-bonding interactions.